Implacable - Campbell, Jack (Naval officer) (Campbell, Jack (Naval officer). Lost fleet: outlands, 2024)
"Admiral John "Black Jack" Geary fears the greatest threat to humanity may be itself in this gripping continuation of the New York Times bestselling series. As far from explored space as any human has ever been, Geary and the Alliance fleet are on their own, protecting a diplomatic mission in territory belonging to an alien species with still unknown motives. His already complex and dangerous mission is further imperiled by deadly challenges from other human factions seeking to threaten or exploit the aliens. When another alien species whose technology is far more advanced than humanity's arrives, the stakes are raised to the highest possible level. But the most serious threat comes from an unexpected source. When presented with orders to carry out actions he believes are not only mistaken but would be contrary to the ideals of the Alliance, Geary has to finally decide whether he must invoke the power that his long-revered name holds, all the while knowing that this might endanger his entire fleet, tear apart the Alliance, and destroy everything he has fought for"--